Analisis Pelaksanaan Manajemen Pelayanan Rumah Sakit terhadap Kepuasan Pasien Rawat Jalan Peserta BPJS di RSUD Cut Nyak Dhien Meulaboh - Desra Erwin Aiyuzi; Asriwati Asriwati; Ramadhani Syafitri Nasution (Universitas Muhammadiyah Manado, 2025)
Patient satisfaction is an important indicator in assessing the quality of hospital services, especially for National Health Insurance (JKN) participants. This study aims to analyze the influence of planning, organizing, implementing, and controlling management functions on the satisfaction of outpatients of BPJS participants at Cut Nyak Dhien Meulaboh Hospital. The approach used was quantitative with a cross sectional design, involving 100 respondents selected through accidental sampling techniques. Data collection was carried out using a closed questionnaire that has been tested for validity and reliability. Data analysis was carried out using a double logistics regression test. The results showed that the four management functions had a significant influence on patient satisfaction (p < 0.05). Among these variables, service implementation was the most dominant factor with an odds ratio (OR) value of 445,949. This shows that the implementation of services that are procedural, fast, and communicative greatly determines the level of patient satisfaction. These findings underscore the importance of service management that is structured, patient-oriented, and supported by continuous evaluation and supervision. Therefore, strengthening the implementation and organizing function needs to be a priority in efforts to improve the quality of services in hospitals.